Nop2 is required for mammalian preimplantation development. Issue 2 (15th December 2015) - Cui, Wei; Pizzollo, Jason; Han, Zhengbin; Marcho, Chelsea; Zhang, Kun; Mager, Jesse
SUMMARY: Nucleolar protein 2 (NOP2) is evolutionarily conserved from yeast to human, and has been found to play an important role in accelerating cell proliferation, cell‐cycle progression, and tumor aggressiveness. The expression pattern and function of Nop2 during early mammalian embryo development, however, has not been investigated. We identified Nop2 as an essential gene for development to the blastocyst stage while performing an RNA interference (RNAi)‐based screen in mouse preimplantation embryos. Nop2 is expressed throughout preimplantation development, with highest mRNA and protein accumulation at the 8‐cell and morula stages, respectively. RNAi‐mediated knockdown of Nop2 results in embryos that arrest as morula. NOP2‐deficient embryos exhibit reduced blastomere numbers, greatly increased apoptosis, and impaired cell‐lineage specification. Furthermore, knockdown of Nop2 results in global reduction of all RNA species, including rRNA, small nuclear RNA, small nucleolar RNA, and mRNA. Taken together, our results demonstrate that Nop2 is an essential gene for blastocyst formation, and is required for RNA processing and/or stability in vivo during preimplantation embryo development in the mouse. Mol. Reprod. Dev. 83: 124–131, 2016. © 2015 Wiley Periodicals, Inc .